Asystole during onyx embolisation of a dural AV fistula: The trigeminocardiac reflex. Issue 2 (April 2019) - Nicholson, Patrick; Hilditch, Christopher; Brinjikji, Waleed; Krings, Timo
There are fewer than 20 published case reports of bradycardia or asystole during intracranial embolisation procedures. These are well described in open neurosurgical procedures, particularly involving the skull base. We present a case of a 59-year-old male patient who presented for elective embolisation of a dural arteriovenous fistula. During the injection of Onyx, the patient experience sudden asystole, which recurred after a second Onyx injection. Following successful treatment, a third injection proceeded without incident.